Late mortality and causes of death among 5-year survivors of childhood cancer diagnosed in the period 1960–1999 and registered in the Italian Off-Therapy Registry. (March 2019) - Bagnasco, Francesca; Caruso, Silvia; Andreano, Anita; Valsecchi, Maria Grazia; Jankovic, Momcilo; Biondi, Andrea; Miligi, Lucia; Casella, Claudia; Terenziani, Monica; Massimino, Maura; Sacerdote, Carlotta; Morsellino, Vera; et al.
Abstract: Introduction: Advances in paediatric oncology led to the increase in long-term survival, revealing the burden of therapy-related long-term side effects. We evaluated overall and cause-specific mortality in a large cohort of Italian childhood cancer survivors (CCSs) and adolescent cancer survivors identified through the off-therapy registry. Materials and methods: CCSs alive 5 years after cancer diagnosis occurring between 1960 and 1999 were eligible; the last follow-up was between 2011 and 2014. Outcomes were reported as standardised mortality ratios (SMRs) and absolute excess risks (AERs). Results: Among 12, 214 CCSs, 1113 (9.1%) deaths occurred. Survival at 35 years since diagnosis was 87% (95% confidence interval [CI]: 86–88) and at 45 years was 81% (95% CI: 77–84). CCSs had an 11-fold increased risk of death (SMR 95% CI: 10.7–12), corresponding to an AER of 48 (95% CI: 45–51). Mortality decreased by 60% for survivors treated most recently (1990–1999). The most frequent causes of death were recurrence of the original cancer (56%), a subsequent neoplasm (19%) and cardiovascular diseases (5.8%). Among those who survived at least 15 years after diagnosis, a secondary malignancy was the leading cause of death. Conclusions: This study confirms the impact of recent advances in anticancer therapy in reducing mortality, mainly attributable to recurrence but also to other causes. However, overall mortality continues to be higher than in the general population. A long-term follow-up is needed to prevent late mortality due to secondary neoplasms and non-neoplastic causes in CCSs. Highlights: Childhood cancer survivors have higher rates of death than their peers in the general population. Late mortality after childhood cancer reduced steadily over the decades between 1960 and 1999. Recurrence of the original cancer is the main cause of mortality in the first 15 years from diagnosis, but afterwards, other causes, primary second malignant tumours and cardiovascular events are the leading cause of death.